Occupational Safety and Health for Technologists, Engineers, and Managers, Global Edition - Goetsch, David L. (Pearson International Content, 2015)
The full text downloaded to your computer With eBooks you can: search for key concepts, words and phrases make highlights and notes as you study share your notes with friends eBooks are downloaded to your computer and accessible either offline through the Bookshelf (available as a free download), available online and also via the iPad and Android apps. Upon purchase, you'll gain instant access to this eBook. Time limit The eBooks products do not have an expiry date. You will continue to access your digital ebook products whilst you have your Bookshelf installed. For all Occupational Safety, Safety and Health Management, and related courses in any safety management, engineering, industrial/manufacturing technology, or other program, in universities, colleges, community colleges, and corporate training settings. This comprehensive, extensively updated text covers all aspects of occupational safety and health in today’s global workplace. A major revision, Occupational Safety and Health for Technologists, Engineers, and Managers, 8th Edition, presents new and revised regulations, emerging approaches and trends, updated statistics, and other new material of significant importance to students and practitioners in the field. Among the dozens of new topics covered: ROI for safety/health investments; Heinrich's theory; Worker's Compensation lawsuits; fall protection; hard hat ratings; PPE for cold work environments; indoor air quality investigations; fungal growth assessment; nanoscale materials; and noise reduction ratings. Clear, up-to-date, and logically sequenced, this text begins with historical perspective and overview, then covers laws and regulations; human elements; hazard assessment, prevention, and control; and key management issues. Each chapter contains case studies to promote classroom discussion; at least one safety fact or myth designed to engage students; and review questions to test mastery and promote critical thinking.   Teaching and Learning Experience This book will help technologists, engineers, and managers quickly master today's best practices for occupational safety and health. It provides:  The most comprehensive coverage available, fully reflecting the field's latest trends: Thoroughly prepares students for current and future realities in the field of occupational safety and health Supported with exceptional pedagogical features: Includes well-crafted chapter summaries, key terms and concepts, review questions, and many boxed features